Connecting social forestry to conservation policies in Tanah Papua - Fatem, Sepus M. (Forest and Society, 2019)
Papua is the region with the largest remaining forest resources in Indonesia. This amounts to 42,224,840 hectares of forest areas, which in other words means that 95% of its total area is listed as forests. The breadth of forest coverage is formalized by Forestry Ministerial Decree of Indonesia no. 891/Kpts-II/1999 on the Designation of Provincial Forest Area and Inland Waters in Tanah Papua. Meanwhile, forest resources plays an important part of people’s lives in Tanah Papua and holds an important function among customary communities in Papua. Nevertheless, as yet there has been no meaningful social forestry program that provides direct benefits to communities. As a response to the special autonomy of Papua, several initiatives aimed at providing formal access and support services to local people in forest resource management. Ironically however, such initiatives are discouraged by the central government, arguing that they should originate from the Ministry of Environment and Forestry. Despite these circumstances, Tambrauw and West Papua have declared themselves to be a conservation district and conservation province, respectively. This article attempts to briefly portray the dynamics of these conservation initiatives and the possibilities of developing synergy with social forestry programming in Tambrauw District and West Papua Province.